Enhanced Photosynthesis and Transpiration in an Old Growth Forest Due To Wildfire Smoke. Issue 10 (20th May 2022) - Rastogi, Bharat; Schmidt, Andres; Berkelhammer, Max; Noone, David; Meinzer, Frederick C.; Kim, John; Still, Christopher J.
Abstract: We document the response of a 2 day wildfire smoke event on a moist temperate coniferous old‐growth forest in the western U.S. Wildfire smoke increased air temperature and suppressed relative humidity and total incoming radiation. Despite these conditions a ∼10% increase in ecosystem photosynthesis was observed. This was explained by a large increase (41%) in ecosystem‐scale stomatal conductance, inferred from measurements of carbonyl sulfide. Increased stomatal conductance contradicts expected stomatal closure at high vapor pressure deficit and was likely caused by an increase in diffuse light and thus shade leaf insolation. Higher ecosystem productivity and transpiration were linked to a greater drawdown of soil moisture. Ecosystem‐scale measurements across a diverse range of ecosystems are needed to better understand the canopy response to wildfire smoke, which is an increasingly common phenomenon across large parts of the world, including the forests of western North America. Plain Language Summary: Increases in wildfire intensity have been observed and projected for large parts of western North America, but the impact of smoke from these wildfires on carbon and water fluxes in different ecosystems is not well understood. In this study, we document the response of an old growth coniferous forest located in Pacific Northwestern U.S. to smoke from a nearby wildfire. During this event, the forest experienced warmer, drier and darker conditions. Using measurements of trace gases in the air we observe that the forest canopy increased photosynthesis and transpiration rates. This was due to an increase in scattering of light by smoke particles and facilitated by abundant soil moisture. Increased water‐use by trees also reduced the temperature of canopy leaves, potentially preventing them from damaging temperatures. We suggest continued measurements at the ecosystem scale to understand the response of diverse ecosystems to wildfire smoke, an increasingly common phenomenon for large parts of the world, including western North America. Key Points: Smoke from a nearby fire warmed and dried the air above an old‐growth forest and decreased incoming radiation Smoke led to higher canopy photosynthesis and transpiration rates, estimated from eddy covariance and carbonyl sulfide profile measurements, respectively These increased fluxes are also facilitated by available deep soil moisture at the site